Income Dependent Equivalence Scales, Inequality, and Poverty - Christian Dudel; Jan Marvin Garbuszus; Notburga Ott; Martin Werding (Center for Economic Studies and ifo Institute (CESifo), 2015)
Most equivalence scales which are applied in research on poverty and inequality do not depend on income, although there is strong empirical evidence that equivalence scales in fact are income dependent. This paper explores the consistency of results derived from income independent and income dependent scales. It is shown that scales of both types inevitably lead to differing assessments of poverty and inequality under quite general conditions. German microdata will be used to demonstrate and illustrate our findings. Our results provide evidence that income independent scales should be replaced with income dependent equivalence scales.
Keywords: C18; D10; I32; 330; equivalence scales; independence of base; income dependence